Ventilation and perceived exertion are sensitive to changes in exercise tolerance: arm+leg cycling vs. leg cycling - Nicolò, Andrea; Girardi, Michele; Bazzucchi, Ilenia; Sacchetti, Massimo; Felici, Francesco (Frontiers in Physiology, 2023)
Purpose: Growing evidence suggests that respiratory frequency (fR) is a marker of physical effort and a variable sensitive to changes in exercise tolerance. The comparison between arm+leg cycling (Arm+leg) and leg cycling (Leg) has the potential to further test this notion because a greater exercise tolerance is expected in the Arm+leg modality. We systematically compared Arm+leg vs. Leg using different performance tests. Methods: Twelve males underwent six performance tests in separate, randomized visits. Three tests were performed in each of the two exercise modalities, i.e. an incremental test and two time-to-exhaustion (TTE) tests performed at 90% or 75% of the peak power output reached in the Leg incremental test (PPOLeg). Exercise tolerance, perceived exertion, and cardiorespiratory variables were recorded during all the tests. Results: A greater exercise tolerance (p < 0.001) was found for Arm+leg in the incremental test (337 ± 32 W vs. 292 ± 28 W), in the TTE test at 90% of PPOLeg (638 ± 154 s vs. 307 ± 67 s), and in the TTE test at 75% of PPOLeg (1,675 ± 525 s vs. 880 ± 363 s). Unlike V˙O2 and heart rate, both fR and minute ventilation were lower (p < 0.003) at isotime in all the Arm+leg tests vs. Leg tests. Furthermore, a lower perceived exertion was observed in the Arm+leg tests, especially during the TTE tests (p < 0.001). Conclusion: Minute ventilation, fR and perceived exertion are sensitive to the improvements in exercise tolerance observed when comparing Arm+leg vs. Leg, unlike V˙O2 and heart rate.